1996
DOI: 10.1007/bf03401646
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Protease Homolog Differentially Expressed in Breast and Ovarian Cancer

Abstract: Protease M expression (mRNA) may be a useful marker in the detection of primary mammary carcinomas, as well as primary ovarian cancers. Other medical applications are also likely, based on sequence relatedness to trypsin and PSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
172
0
17

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(200 citation statements)
references
References 37 publications
(24 reference statements)
9
172
0
17
Order By: Relevance
“…The most widely used marker, CA125, has shown merit in pilot screening studies and ovarian cancer management, but the sensitivity for early-stage disease before clinical detection remains questionable (Bast et al, 1998). We have previously identified by differential display a cDNA that is highly expressed in ovarian tumour (Anisowicz et al, 1996). Sequence analysis has shown that this novel protein belongs to the human kallikrein protein family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most widely used marker, CA125, has shown merit in pilot screening studies and ovarian cancer management, but the sensitivity for early-stage disease before clinical detection remains questionable (Bast et al, 1998). We have previously identified by differential display a cDNA that is highly expressed in ovarian tumour (Anisowicz et al, 1996). Sequence analysis has shown that this novel protein belongs to the human kallikrein protein family.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously identified by differential display a cDNA sequence that is highly expressed in primary breast and ovarian tumour tissues and cell lines (Anisowicz et al, 1996). The encoded protein, which originally was named as protease M, shows strong homology to the human kallikrein (hK) family proteins (for a review see Schachter, 1980;) and has a revised nomenclature of kallikrein 6 (KLK6 for the gene and hK6 for the encoded protein).…”
mentioning
confidence: 99%
“…Previously called zyme (Little et al, 1997), protease M (Anisowicz et al, 1996), and neurosin (Yamashiro et al, 1997), kallikrein 6 is now the accepted name (Diamandis et al, 2000b). hK6 is a trypsin-like serine protease of unknown physiologic function that is secreted as a 223 amino acid protein.…”
mentioning
confidence: 99%
“…Investigations are proceeding as sensitive and specific assays measuring the gene expression or protein mass of each newly identified member of the kallikrein family become available. Tissue expression of the kallikreins examined to date appears to be down-regulated in aggressive forms of breast cancer (hK3 (PSA) (Levesque et al, 1998), hK10 (Liu et al, 1996;Goyal et al, 1998), hK13 (Yousef et al, 2000) and hK6 (Anisowicz et al, 1996)) and up-regulated in ovarian cancer (hK4 (Obiezu et al, 2002), hK10 (Luo et al, 2001), hK5 (Kim et al, 2001), hK8 (Magklara et al, 2001) and hK6 (Tanimoto et al, 2001)). …”
mentioning
confidence: 99%
“…Many new reports have shown that various members of the kallikrein gene family are differentially regulated in cancer. Specifically, the stratum corneum chymotryptic enzyme (KLK7), neuropsin (KLK8) and zyme (KLK6) have been shown to be overexpressed in ovarian tumours (Anisowicz et al, 1996;Tanimoto et al, 1999;Underwood et al, 1999) while the normal epithelial cell-specific 1 gene (NES1; KLK10) is down-regulated (Liu et al, 1996;Goyal et al, 1998).…”
mentioning
confidence: 99%